2006
DOI: 10.3928/15428877-20060901-05
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Assessing Surgical Competency in Ophthalmology Training Programs

Abstract: <H4>BACKGROUND AND OBJECTIVE</H4> <P> The Accreditation Council for Graduate Medical Education (ACGME) has mandated implementation of six new competencies in resident training in the United States. An implementation strategy is proposed to teach and assess cataract surgical competence. </P> <H4>PATIENTS AND METHODS</H4> <P> An intradepartmental Task Force for the ACGME competencies reviewed the literature for assessment tools to develop an implementation matrix for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…This hypothesis was, in part, based on evidence that beginners can experience significant amounts of extra stress in the operative environment, and this can actually impact negatively on performance slowing down their functioning and learning process 15 17. In addition, trainers frequently describe the training of the most junior surgeons as one of the most stressful aspects of their role, and so a programme, as the one described here, may prove more broadly beneficial.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This hypothesis was, in part, based on evidence that beginners can experience significant amounts of extra stress in the operative environment, and this can actually impact negatively on performance slowing down their functioning and learning process 15 17. In addition, trainers frequently describe the training of the most junior surgeons as one of the most stressful aspects of their role, and so a programme, as the one described here, may prove more broadly beneficial.…”
Section: Discussionmentioning
confidence: 95%
“…Highly structured, supervised and assessed wet-lab sessions on animal models and compulsory microsurgical skill courses offer an additional training environment. This model, however, has a more limited ability to objectively track improvement 15. The more frequent use of VR simulators for surgical training could address some of these limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic literature review, it was suggested the use of a laboratory to teach and assess aspects of resident surgical competence [12]. In another study, specific techniques for teaching and assessing surgical competence in ophthalmology residencies were suggested, such as: written and explicit goals or objectives for each stage of training and the use of formative rather than summative feedback [13]. Golnik et al developed a 1-page on-call assessment tool (OCAT) and scoring rubric to evaluate ophthalmology resident on-call performance.…”
Section: Introductionmentioning
confidence: 99%
“…Several standardized instruments have been developed to evaluate resident surgical skills [2124]. The Global Rating Assessment of Skills in Intraocular Surgery (GRASIS) is a 1-page evaluation form that has been validated and may be used for any intraocular procedure [22].…”
Section: Structured Curriculum For Glaucoma Surgerymentioning
confidence: 99%